CONSTITUENT AND ANTIHYPERURICEMIC ACTIVITY OF STELECHOCARPUS BURAHOL LEAVES SUBFRACTIONS - Sunarni, Titik; Fidrianny, Irda; Iwo, Maria Immaculata; Wirasutisna, Komar Ruslan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The goal of this research was to evaluate antihyperuricemic activity of Stelechocarpus burahol leaves subfractions and isolate its chemicalÂ constituent of active subfraction. Methods: Ethyl acetate fraction from S. burahol extract was subfractionated by vacuum liquid chromatography, and the active subfractions wereÂ further subfractionated by classic column chromatography using isocratic eluent, followed by isolated chemical constituent from active subfraction.Â Hyperuricemic rat model was induced by given potassium oxonate intraperitoneally. The inhibitory effect of subfractions on the xanthine oxidase (XO) activity was determined using ultraviolet-visible spectrophotometry method. Results: Subfractions E.3, E.4, and E.5 significantly (p<0.05) reduced the serum uric acid (UA) level 43%, 46%, and 33%, respectively. The E.3, E.4, andÂ E.5 have showed very weak XO inhibitory activity. Subfraction E.3.2 and E.4.3 significantly (p<0.05) reduced the serum UA level 29% and 38%, respectively,Â however still very weak effect on XO activity. Chemical constituent which was isolated from subfraction E.4.3 was kaempferol-3-O-rhamnoside. Conclusion: The subfractions of ethyl acetate fraction had antihyperuricemic activity in vivo but less effect on XO activity in vitro. Isolated compoundÂ in active antihyperuricemic of subfraction E.4.3 was kaempferol-3-O-rhamnoside. Keywords: Stelechocarpus burahol, Subfraction, Antihyperuricemic, Xanthine oxidase inhibitory activity, Kaempferol-3-O-rhamnoside.